Computer Assisted Audit Tools and Techniques Adoption: A Systematic Literature Review - Nasrah, Hidayati; Muda, Iskandar; Kesuma, Sambas Ade (International Journal of Social Service and Research, 2023)
Computer Assisted Audit Techniques and Tools (CAATTs) are a form of innovation in the field of technology in the world of accounting, CAATTs have become fundamental in many audit methodologies. However, there is still very little information regarding these CAATTs. This research is based on increasing knowledge about the success of CAATTs, this is useful for analyzing implementation and operational problems with a broader understanding of the practices contained in internal audit departments that use CAATTs technology. Therefore, we present a systematic literature review on the factors that determine an auditee to use CAATTs technology. This research was conducted using a qualitative analysis of the things that influence an audit to use CAATTs in the auditing process based on previous studies. The findings from this study indicate that what influences an audit to use CAATTs is time efficiency, work effectiveness, auditor confidence, company partners, processing accuracy, techniques and services, purchase costs, understanding of using CAATTs, background of the audit itself, motivation to learning, performance expectations, characteristics of the audit team, support or coercion, and facilities.